Intervensi Fonetik Bahasa Arab dan Bahasa Indonesia (Studi Kontrastif Bahasa Arab dan Indonesia Pada Tataran Pelafalan Kata) - Qomaruddin, Farid; Haq, Muhammad A’inul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2022)
Linguistic phenomena that cause problems for foreign language learners cannot be separated from the inherent characteristics of each source language and target language, especially for some of the elements of both which are different from one another. This study aims to reveal several forms of phonological intervention in Arabic against Indonesian or vice versa as well as a model of changing the phonetic level between the two. The methodology in this research is library research. Sources of data come from several literatures that are closely related to the topic obtained through documentation techniques, which are then analyzed using qualitative descriptive techniques. The findings of this study are that the level of intervention of Indonesian sounds into Arabic is found in the eight forms of speech sounds that change. In contrast, the Intervention of Arabic into Indonesian is found in nine forms of speech.